Namdeutsch und Namslang.: Mehrsprachige und multimodale Online-Kommunikationsformen in der namibischen Varietät des Deutschen - Verdiani, Silvia (Linguistik Online, 2025)
Namdeutsch and Namslang are two German-based non-standard varieties that contain loanwords from Afrikaans, English and indigenous languages. Their development began during German colonial rule in German South West Africa, now Namibia. Namdeutsch is a linguistic variant that has become established among German-speakers in Namibia in recent decades, while Namslang or NAM Släng has recently become widely used online by Namibian German-speaking youth communities. My paper focuses on differently marked multimodal online communication to identify and describe typical features of German diversity in Namibia. It will also identify the role of digital multimodality, based on the interaction of visual and linguistic material, in the constitution of meaning in this context. The aim is to examine how this comes to light through the online press and bilingual/trilingual conversations in social networks, and how speaker identities in social media are (co-)constructed through the varieties of Namdeutsch and Namslang. The research is based on the Facebook page and the NAM Släng dictionary of the musician EES (Eric Sell), the glosses of the online edition of the Allgemeine Zeitung and the Deutsch in Namibia (DNAM) corpus.